Phytoplankton blooms in the vicinity of palmer station, Antarctica - Holm-Hansen, Osmund; Mitchell, Brian Gregory; Hewes, Christopher D; Karl, David Michael (Polar Biology, 1989)
Fifteen oceanographic stations were occupied in the vicinity of Anvers Island, Antarctica, in January of 1985 and 1987. All stations showed high phytoplankton biomass (4.0 to 30 μg chl-a/liter) which was either uniformly distributed in the upper mixed layer or showed a pronounced sub-surface maximum at 4–5 m depth. As phosphate was less than 0.02 μm and nitrate about 2.0 μm in surface waters, it appears that nutrient limitation of phytoplankton growth may be of importance during such blooms. This view is supported by chemical measurements of the particulate material which showed high chl-a/ATP ratios (about 7.7), as well as high POC/ATP ratios (about 700). Microscopical analysis revealed a dominance of large-celled diatoms and the near absence of heterotrophic protozoans. Size fractionation studies showed that the nanoplankton accounted for only 28% of the total phytoplankton biomass. When phytoplankton biomass reaches the levels found at these stations, it appears that the cells are light-limited and hence dark-adapted, which results in the high chl-a/ATP ratios and the low assimilation values (0.49–1.64) obtained in our studies. Under such conditions greater than 50% of the total phytoplankton biomass is found below the 1% light level.
Keywords: Sørishavet; biomasse; fytoplankton; oseanografi

Icebergs rework shelf sediments to 500 m off Antarctica - Barnes, Peter W.; Lien, Reidar (Geology, 1988)
Icebergs and sea ice rework the sediments of high-latitude shelves, producing modern diamicts (ice-keel turbates) unrelated to glacial proximity. Off Antarctica, sidescan sonar data indicate the presence of ice-gouge features formed by the physical interaction between ice keels and the sea bed. These are recognized as incisions a few metres deep and tens of metres wide, in water depths up to 500 m. On the submarine bank tops and slopes off Wilkes Land and in the Weddell Sea, subcircular depressions 30 to 150 m in diameter, a washboard pattern, and hummocky bed features also represent iceberg-resting sites. The freshness of sea-bed morphology, nearby Holocene sediment ponding, and active hydraulic sedimentary processes indicate that the sea floor is being reworked by iceberg keels. Tabular iceberg drafts in excess of 330 m have been measured, and modeling studies suggest that nontabular iceberg drafts of 500 m are possible. We conclude that a modern ice-keel turbate deposit in the form of a poorly stratified diamicton is probably widespread on that part (54%) of the Antarctic shelf less than 500 m deep.
Keywords: Sørishavet; Weddellhavet; geofysikk; geologi; isberg; issfjell; oseanografi

Notes on Southern Ocean hydrography, sea-ice and bottom water formation - Foldvik, Arne; Gammelsrød, Tor (Palaeogeography, Palaeoclimatology, Palaeoecology, 1988)
The Southern Ocean circulation and sea-ice distribution is briefly described. The formation of extremely cold bottom water in the Weddell Sea and its relation to the floating Ronne-Filchner Ice Shelves is discussed. It is shown that a concentrated swift eroding bottom current with anomalous low ratio transports the cold and dense ice Shelf Water from the shelf towards large depths. Comments are made on possible implications of this process for the large-scale deep-water circulation and for the interpretation of sediment cores.
Keywords: Sørishavet; Weddellhavet; geofysikk; havis; havstrømmer; hydrografi; isshelf; oseanografi

Palaeoceanography of the subantarctic South Atlantic - Ciesielski, Paul; Kristoffersen, Yngve (Nature, 1987)
Keywords: Sørishavet; oseanografi

Photoadaptation in Antarctic phytopfankton: variations in growth rate, chemical composition and P versus I curves - Sakshaug, Egil; Holm-Hansen, Osmund (Journal of Plankton Research, 1986)
The response of phytoplankton to variations in the light regime was studied during the VULCAN and ACDA cruises in the Antarctic. Unenriched batch cultures of 12–19 days' duration reached chl concentrations of 10–50 μg−1 and exhibited exponential growth rates, with the maximal rate being 0.41 doubl, day−1. Ice edge algae exhibited maximum growth rates at photon flux densities (PFD) of 30–100 μE m−2S−1 and the growth rate was reduced by about 30% at 500–1000 μE m−2S−1 The chl/C ratio ranged between 0.004 and 0.018, with the lowest ratios at PFDs above 500 μE m−2S−1 chl/C ratios were also below maximum at PFDs below 40–50 μE m−2S−1 The C:N:P ratios were close to the Redfield ratios; the Si/C ratio averaged 0.16 (atoms), and the ATP/C ratio averaged from 0.0024 to 0.0050 in different culture senes. When thawed after having been frozen for 10 days, shade-adapted cultures were in a much better condition than sun-adapted ones. P versus I data showed that the maximum assimilation number varied from 0.75 to 4.4 μg C (μg chl)−1h−1. It varied inversely with the chl/C ratio; therefore the maximum carbon turnover rate varied little between samples (0.024/0.035 h−1). Low biomass communities exhibited relatively high values for α (the initial slope of P versus I curves), low values for 1sat (160–330 μE m−2S−1), and they were susceptible to photoinhibition. In contrast, communities dominated by Odontella weissflogii exhibited low values for α, a high value for Isat (560 μE m−2S−1 and they tolerated high PFDs. The photo-adaptational status of the phytoplankton in natural water samples is discussed relative to the profile of water column stability and mixing processes.
Keywords: Sørishavet; alger; biokjemi; fytoplankton; marin biologi; oseanografi; planteplankton

Aleksandr Stepanovich Kuchin: the Russian who went south with Amundsen - Barr, William (Polar Record, 1985)
Aleksandr Stepanovich Kuchin (1888–1912) was already an experienced mariner and oceanographer when Amundsen invited him to join the Fram expedition of 1910–12. Expecting a voyage through the Barents Sea, Kuchin found himself on an expedition to the Antarctic. While Amundsen's sledging parties sought the South Pole, Kuchin remained with the ship, completing an excellent oceanographic survey of the southern Atlantic Ocean. Returning to Russia in 1912 he was recruited, by the geologist and explorer V. A. Rusinov to join a scientific expedition to Svalbard. As deputy leader of the party and captain of Gerkules, the expedition ship, Kuchin played an important role in the Svalbard survey. Then once again found himself heading in an unexpected direction: on completing the Svalbard work, Rusanov decided to attempt the Northern Sea Route to the Bering Strait. Gerkules disappeared and was never seen again; her loss, presumably in the Kara Sea, brought to an untimely end the career of a promising young polar explorer.
Keywords: Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; biografier; oseanografi; polarområdene

Hydrographic observations on the southern Weddell Sea shelf break - Foldvik, Arne; Gammelsrød, Tor (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; hydrografi; oseanografi

Oceanographic conditions on the Weddell Sea Shelf during the German Antarctic Expedition 1979/80 - Foldvik, Arne; Gammelsrød, Tor; Slotsvik, Noralf; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; hydrografi; isshelf; oseanografi

Circulation and Water Masses on the Southern Weddell Sea Shelf - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Oceanology of the Antarctic Continental Shelf, 1985)
Keywords: Sørishavet; Weddellhavet; forskning; havstrømmer; oseanografi

Physical oceanography studies in the Weddell Sea during the Norwegian Antarctic Research Expedition 1978/79 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; havstrømmer; hydrografi; isshelf; oseanografi

The antarctic diatoms Thalassiosira dichotomica (Kozlova) comb. nov. and T. ambigua kozlova - Fryxell, Greta A.; Hasle, Grethe Rytter (Polar Biology, 1983)
Two small antarctic diatoms, usually missed by traditional collection methods, have been studied in light and electron microscopes. Porosira dichotomica has been transferred to Thalassiosira since its valve structure and process pattern agree better with that genus. T. dichotomica is unusual in that some lines of areola walls are extended, sail-like, out from the valve, supporting Kozlova's original drawings. T. ambigua, the smaller of the two, has many similarities in structure with T. dichotomica, but has granules on the margin, lacks the sail-like structures on the valve, and has minor differences in processes and areola size. Bands stay together in T. ambigua and show more fine structure than many species in the genus.
Keywords: Sørishavet; diatomeer; marin biologi; oseanografi

The response of Antarctic icebergs to ocean waves - Wadhams, Peter; Kristensen, Monica; Orheim, Olav (Journal of Geophysical Research: Oceans, 1983)
The heave, tilt, and strain responses of three Antarctic tabular icebergs to ocean waves were measured during a 1980–1981 cruise of HMS Endurance to the South Atlantic. The three icebergs, located near the South Sandwich and South Orkney islands, were instrumented with accelerometers, tiltmeters, and wire strainmeters, while a Waverider buoy was used to record the ocean wave field. The thickness of the icebergs was surveyed by a helicopter-borne radio echo sounder. The heave response occurred mainly at the swell period but with outbreaks of bobbing which lasted for a few cycles at a resonant period (about 40 s), which agreed well with the predictions of a numerical finite element model. The roll response occurred mainly at a long resonant period (40–50 s), which again agreed well with the model, but there was also a significant response at ocean wave periods (5–20 s), which exceeded predictions. The strain response had a component at very long periods, which is unexplained by theory, while the surface strain at ocean wave periods agreed with the simple analytical model of Goodman et al. (1980). Using this model it is possible to predict a wave height and period that will cause breakup of the icebergs, and we conclude that swell-induced breakup is likely to occur during major storms in the open southern ocean.
Keywords: Sør-Orknøyene; Sørishavet; brehylle; geofysikk; glasiologi; havbølger; isberg; isbreer; isbrem; isfjell; isshelf; oseanografi

Analysis of wave measurements at Bouvetøya - Arntsen, Øivind A; Snuggerud, John (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; ekspedisjoner; forskning; oseanografi

Hydrographic surveying around Bouvetøya - Fjørtoft, Jon H (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; hydrografi; oseanografi

Measurements of ocean current and bottom pressure near Bouvetøya, January–March 1979 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; havstrømmer; oseanografi

Hydrographic and current measurements in the southern Weddell Sea 1979/80 - Gammelsrød, Tor; Slotsvik, Noralf (Polarforschung, 1981)
During the 1979-1980 expediton with the icebreaker Polarsirkel we had an excellent opportunity to study the physical oceanography of the inner part of the Weddell Sea. The ship followed the ice shelf barrier from Cape Norwegia at about 15 °W, and due to favourable ice conditions, it was able to penetrate all the way to the Antarctic Peninsula (60 0W). In this preliminary report we give a review of the physical oceanography programme which mostly consists of hydrographic (CTD) stations near the barrier, and also sorne current and water level measurernents. The different water masses observed are described and the possibility for a tidal-drlvcn upwelling near the ice shelf barrier is indicated.
Keywords: AABW; Sørishavet; Weddellhavet; bunnvannet; havis; hydrografi; isshelf; oseanografi; sjøis; sjøvann; vannmasser

Flow Around Icebergs - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; isberg; observasjoner; oseanografi; sjøvann

Some satellite tracked iceberg drifts in the Antarctic - Vinje, Torgny E (Annals of Glaciology, 1980)
Keywords: Sørishavet; drivis; havis; isberg; isdrift; isfjell; oseanografi; sjøis; vannmasser